2006
DOI: 10.1007/s00535-006-1782-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of one week of carvedilol administration on cirrhotic rats

Abstract: Carvedilol decreased portal pressure through a reduction of splanchnic blood flow associated with a decrease in hepatocollateral resistance. Additionally, administration of carvedilol decreased endothelial-related vasodilatory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Carvedilol may be the optimal choice for beta-blockade in patients with ESLD. It has been demonstrated to cause a reduction in portal pressure through decreased splanchnic blood flow and decreased portocollateral resistance (66,67). Carvedilol has also been shown to be superior to other beta-blocking agents in reducing the hepatic venous pressure gradient (66,68).…”
Section: Pre-operative Cardiovascular Assessment and Managementmentioning
confidence: 98%
“…Carvedilol may be the optimal choice for beta-blockade in patients with ESLD. It has been demonstrated to cause a reduction in portal pressure through decreased splanchnic blood flow and decreased portocollateral resistance (66,67). Carvedilol has also been shown to be superior to other beta-blocking agents in reducing the hepatic venous pressure gradient (66,68).…”
Section: Pre-operative Cardiovascular Assessment and Managementmentioning
confidence: 98%
“…All rats were anesthetized with 100 mg/kg ketamine. PVP and Q SMA were then measured [22,23]. Additionally, blood samples were collected for liver function (ALT, AST, ALKP, cGT and total bilirubin) measurements.…”
Section: Experiments 1: Hemodynamic and Liver Function Measurementsmentioning
confidence: 99%
“…The effect of reduced intrahepatic resistance may have an additional portal hypotensive effect. Animal studies using bile duct ligated rats have shown that carvedilol reduces portocollateral resistance and endothelial-related vasodilatation in the splanchnic circulation because of reduced expression of eNOS [36]. The effect of carvedilol on the splanchnic circulation probably reflects a dynamic interplay between a receptor-mediated vasoconstriction and endothelial-related vasodilatation, with the net effect being splanchnic vasoconstriction.…”
Section: Introductionmentioning
confidence: 97%
“…Potentially, the beneficial effects of unopposed a receptor stimulation on the splanchnic circulation may be somewhat less with carvedilol. However, animal studies have shown that splanchnic blood flow is reduced with carvedilol [36]. This may reflect the relatively weak and incomplete a blocking actions of carvedilol on the splanchnic circulation, not enough to counteract the strong blockade of b 2 receptors.…”
Section: Introductionmentioning
confidence: 97%